THE REPRESENTATION OF THE CONCEPT “MIND” IN ENGLISH AND KARAKALPAK PROVERBS - Ulimbetova, Dinara Bekbergenovna; Xudaibergenov, Azamat Abdikalikovich (SCIENCE and SOCIETY, 2026)
This article examines the concept of “mind” through a comparative linguocultural analysis of English and Karakalpak languages. Drawing on proverbs, idioms, and folk narratives, the study identifies both shared and culturally distinct patterns in how cognition is conceptualized. The main goal is to explore how two typologically distant languages reflect differing yet equally value-laden attitudes toward thought, reason, and mental activity.